Pragmatic policy in Brazil: The political economy of incomplete market reform - Armando Castelar Pinheiro; Régis Bonelli; Ben Ross Schneider (Institute for Applied Economic Research (ipea), 2015)
The last 20 years were a period of major political, economic, social, and institutional reform in Brazil. In the first half of the 1990s, reformers opened the economy to foreign trade and both direct and portfolio investment, sold off a number of large and traditional state-owned enterprises, discontinued myriad price and output regulations, and gradually erected a new regulatory framework. Except for trade liberalization, which was largely completed by the mid-1990s, reforms accelerated after the Real Plan. The consolidation of price stability and market-oriented reforms, in turn, required a number of institutional changes including the strengthening and/or creation of competition and regulatory agencies, and the enactment of new legislation to promote fiscal discipline, improve regulation of financial markets, and protect consumers. This paper focuses on this gradual, piecemeal, loosely coordinated process of partial state retrenchment. The analysis focuses especially on the relative roles of ideology, policy packaging, and pragmatism in advancing reforms; how well reform implementation went; to what extent their results were as expected; and whether state retrenchment is here to stay. We argue that pragmatism - understood as a conduct that emphasizes practicality and stresses practical consequences as constituting the essential criterion in determining action - has been the main driving force behind reforms. In contrast to other Latin American countries, ideology and politics have played a lesser role in fostering market reforms in Brazil. In particular, although reforms were often bundled together with other urgent or popular policies, to facilitate their approval, they were not enacted as a coherent, overall change in development strategy, and more as a piecemeal, flexible, mostly disconnected reform process. Pragmatism led to market reforms that, as a rule, were gradual, usually incomplete and only loosely coordinated with one another. Although these characteristics sometimes facilitated reform politics - opening windows of opportunity and reducing political opposition - they also reduced the efficacy of reforms. In particular, pragmatism was insufficient to generate complementary, second-generation reforms. The overall impact of reforms has not been significant in Brazil, with only a marginal acceleration in GDP growth, due entirely to higher productivity growth. To the extent that pragmatism reflects an approach in which the end results are the main justification for reform, the failure to spur growth after over a decade of reforms puts their sustainability at risk.
Keywords: O11; O54; 330